Analized Factors Influencing The Coverage Of Clinical Competency Target Of Midwifery Student Of Diploma Iii In Relating To Midwifery Clinical Practice - Sugih Wijayati; Elisa Ulfiana; Sri Sumarni (Jurnal LINK, 2012)
The goal of this study is to analyze factors influencing the coverage of clinical competency target of midwifery student of Diploma III in relating to midwifery clinical practice. This study is analytical study with cross-sectional approach. Population in this study is all of the third year's students at Midwifery diploma III of Semarang. There are 80 students involving in this study that has finished midwifery clinical practice. Technical sampling which was run in this study is accidental sampling. The study shows that there are relations between skill competency before clinical practice, preconference running program, and midwifery running progress, student attitude, skill evaluation, academic supervising, and clinical instructor supervising to the coverage of clinical competency target.